2021
DOI: 10.3390/jmse9101120
|View full text |Cite
|
Sign up to set email alerts
|

Ship Deficiency Data of Port State Control to Identify Hidden Risk of Target Ship

Abstract: In the new inspection regime (NIR) of port state control (PSC), the criteria for being judged as a standard risk ship (SRS) is too broad. Some ships are classified as SRS even though they have a large number of ship deficiencies. This paper develops a selection system to identify the hidden risk of target ships in the SRS category using PSC inspection records. This system allows the target ship to be used to help reduce cases of flags being greylisted or blacklisted, which can cause huge shipping losses. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…The model was developed using data from the Tokyo MoU Port State Control (PSC) regime. Shen et al (2021) employed fuzzy importance-performance analysis (F-IPA) and TOPSIS to examine data on ship deficiencies taken from the Tokyo MoU database. conducted a traditional analysis of PSC reports from March 2012 to April 2016, designed as a methodical process for assessing and evaluating printed and electronic documents.…”
Section: Evidence On Inspections and Deficienciesmentioning
confidence: 99%
“…The model was developed using data from the Tokyo MoU Port State Control (PSC) regime. Shen et al (2021) employed fuzzy importance-performance analysis (F-IPA) and TOPSIS to examine data on ship deficiencies taken from the Tokyo MoU database. conducted a traditional analysis of PSC reports from March 2012 to April 2016, designed as a methodical process for assessing and evaluating printed and electronic documents.…”
Section: Evidence On Inspections and Deficienciesmentioning
confidence: 99%
“…The most Data 2022, 7, 60 3 of 13 commonly used fuzzy numbers are triangular and trapezoidal fuzzy numbers [38]. In the existing literature, studies have demonstrated that the applications of the fuzzy set theory contribute to risk assessment methods and safety-related decision-makings in the real-world [39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…The enumeration of flags that meet the standards for low-risk ships is for the Tokyo MOU process only. Thus, for the purposes of compiling the set list, flags of the Tokyo MoU white list who have completed the Voluntary Ecological Audit of IMO member states (VIMSAS) 1554 have been dictated to inform in writing the Tokyo MoU Secretariat for the completion of the VIMSAS check, for the proper recognition of the NIR compliance 1555 .…”
Section: Development Of Pscmentioning
confidence: 99%